The minimum cost D-geodiverse anycast routing with optimal selection of anycast nodes - de Sousa, Amaro (2019)
Consider a geographical network with associated link costs. In anycast routing, network nodes are partitioned into two sets - the source nodes and the anycast (destination) nodes - and the traffic of each source node is routed towards the anycast node providing the minimum routing cost path. By considering a given geographical distance parameter D, we define an anycast routing solution as D-geodiverse when for each source node there are two routing paths, each one towards a different anycast node, such that the geographical distance between the two paths is at least D. Such a solution has the property that any disaster with a coverage diameter below D affecting one routing path (but without involving neither the source node nor its entire set of outgoing links) cannot affect the other path, enhancing in this way the network robustness to natural disasters. The selection of the anycast nodes has an impact both on the feasibility and cost of a D- geodiverse anycast routing solution. Therefore, for a desired number of anycast nodes R, we define the minimum cost D- geodiverse anycast problem (MCD-GAP) aiming to identify a set of R anycast nodes that obtain a minimum cost routing solution. The problem is defined based on integer linear programming and is extended to consider the existence of vulnerability regions in the network, i.e., by imposing the geographical distance D only between network elements belonging to the same region. We present computational results showing the tradeoff between D and R in the optimal solutions obtained with and without vulnerability regions.